Inhibition Effect of Some Algerian Sahara Medicinal Plants on Calcium Oxalate Crystallization - Sekkoum, K.; Cheriti, A.; Taleb, S.; Belboukhari, N.; Djellouli, H.M. (Asian Journal of Chemistry, 2010)
The inhibition effect of six medicinal plants used in Algerian Sahara traditional pharmacopoeia on the calcium oxalate crystallization is studied. The inhibiting effect of two concentrations (0.5 and 1 mg/mL) of each extract and compared without extract. The turbidimetric parameters were given such as the time of induction (Δt), turbidimetric slopes of crystalline growth and aggregation, the coefficient of variation CV % and the rate of inhibition I % for each tests. The results showed that the aqueous extract of Cynodon dactylon L presents an inhibiting effect of a rate of 20 % on the crystalline growth and 60 % on the phase of aggregation, whereas the aqueous extract of Quercus prinus has an inhibiting effect of crystalline aggregation with a rate of 40 %. The aqueous extract of Punica granatum L under the concentration 1 mg/mL, exerts an inhibiting effect of crystalline aggregation but does not influence the crystalline growth. The other extracts did not show any effect on calcium oxalate crystallization.